Experience in the Design and Production of Recombinant Oral Vaccine «Revax VZT» - A. I. Terent’ev; V. A. Zhukov; Ar. A. Sergeev; S. B. Pastushenko; S. V. Rоgоzhkina; S. V. Borisevich; V. A. Maksimov; Al. A. Sergeev; K. A. Titova; D. O. Galakhova (Проблемы особо опасных инфекций, 2019)
Objective of the work was the production of recombinant vaccine «RevaxVZT» in tablet dosage form against hepatitis B and pathogenic for humans orthopoxviruses for further clinical trials. Materials and methods. Recombinant strain b7.5S2-S of vaccinia virus carrying a DNA fragment of hepatitis B virus inserted into thymidinekinase gene was used as an active component of the vaccine. Microbiological, virological, physical, physical and chemical, and biotechnological methods were used for studying the quality of the drug and technological processes. Results and discussion. Results of technological control for semi-finished products and final products of the vaccine “Revax VZT” showed the possibility of using certified hardware-processing line of “TEOVac” for its manufacturing. Same technology can be potentially used with other live tableted embryo smallpox vaccines too. For the development of the vaccine “Revax VZT” with the specific activity of not less than 1.0·107 PFu/tablet, it is necessary to use a dry virus-containing material with activity not less than 2.0·108 PFU/g which is produced by freeze-drying of liquid virus-containing preparation with the activity of not less than 1.0·108 PFU/g, preferentially propagated from chorionic allantoic membranes of chicken embryos as a substrate for viral biomass accumulation.